Integrated Reporting pada Perusahaan Perbankan - Rejeki, Dewi (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2025)
The purpose of this study is to test and analyze the influence of Gender Diversity, Audit Quality and Firm Age on Integrated Reporting. This research was conducted on Banking Companies listed on the Indonesia Stock Exchange (IDX) for the period 2018-2022. The population is 43 companies with a sample obtained from 13 companies based on purposive sampling so that as many as 65 research data are available for processing. The data source is in the form of secondary data taken from the company's annual report . The research method is used with a quantitative approach, which includes descriptive analysis, classical assumption test, multiple linear regression, and hypothesis test. The analysis process was carried out using data processing software, namely SPSS Version 27 and Microsoft Excel 2021. The results of the study show that simultaneously Gender Diversity, Audit Quality and Firm Age have a positive and significant effect on Integrated Reporting. Partially, only Quality Audit has no effect on Integrated Reporting. Meanwhile, Gender Diversity and Firm Age have a positive and significant effect on Integrated Reporting.